The Role of National Resilience in Maintaining National Sovereignty Amidst the Current of Globalization - Ridwan Rivaldo A.; Rifai Fahreza M. (Aimmah: Social Sciences Journal, 2026)
Amidst the tide of globalization that encourages market, technology, and idea integration, Indonesia's sovereignty faces multidimensional threats, ranging from the potential weakening of economic sovereignty and constitutional law tochanges in citizens' attitudes towards ideologies that conflict withPancasila. This study aims to analyze the strategic role of National Resilienceand National Defense in maintaining the integrity and stability of the nationfrom various complex non-military threats (such as ideological radicalism, economic crisis, and cyber attacks). Using qualitative methods on the latest scientific articles (2020-2025), this study shows that Ketnas is a fundamental condition that becomes afortress of defense. The results of the study confirm that Ketnas is actualized through the strengthening of ideological aspects (Pancasila) supported byCivic Education and State Defense Education to shape the character of the nation; as well as through contemporary legal policy to overcome security risksand promote economic stability. The conclusion shows that National Resiliencemust be strengthened holistically, including in the dimension of regional diplomacy (GNB), in order to ensure that the nation's sovereignty is maintainedwisely and sustainably amid global dynamics.